Common variants in breast cancer risk loci predispose to distinct tumor subtypes - Ahearn, Thomas U; Zhang, Haoyu; Michailidou, Kyriaki; Milne, Roger L; Bolla, Manjeet K; Dennis, Joe; Dunning, Alison M; Lush, Michael; Wang, Qin; Andrulis, Irene L; Anton-Culver, Hoda; Arndt, Volker; et al. (Springer Science and Business Media LLC, 2022)
Genome-wide association studies (GWAS) have identified multiple common breast cancer susceptibility variants. Many of these variants have differential associations by estrogen receptor (ER) status, but how these variants relate with other tumor features and intrinsic molecular subtypes is unclear.
Keywords: Breast cancer; Etiologic heterogeneity; Genetic predisposition; Common breast cancer susceptibility variants